Impact of preprocedure simethicone on adenoma detection rate during colonoscopy: a multicenter, endoscopist-blinded randomized controlled trial - Bai, Yu; Fang, Jun; Zhao, Sheng-Bing; Wang, Dong; Li, Yan-Qing; Shi, Rui-Hua; Sun, Zi-Qin; Sun, Ming-Jun; Ji, Feng; Si, Jian-Min; Li, Zhao-Shen (Endoscopy, 2018)
Background and study aims Ideal bowel preparation for colonoscopy requires complete removal of fluid and foam from the colon. Polyethylene glycol (PEG) is widely used for bowel preparation, with antifoaming agents such as simethicone commonly used in combination with PEG. Data on the effect of simethicone on the adenoma detection rate (ADR) were limited. This study therefore aimed to investigate whether preprocedure simethicone could increase the ADR. Patients and methods This was a prospective, multicenter, endoscopist-blinded randomized controlled trial involving consecutive patients who underwent colonoscopy in six centers in China. Patients were randomly assigned to one of two groups: PEG plus simethicone or PEG alone. The primary outcome was ADR; secondary outcomes were quality of bowel preparation, measured by the Boston bowel preparation scale (BBPS) and bubble scores.Results 583 patients were included. More adenomas were detected in the PEG plus simethicone group than in the PEG alone group (ADR 21.0 % vs. 14.3 %, P = 0.04; advanced ADR 9.0 % vs. 7.0 %, P = 0.38). The mean number of adenomas detected was 2.20 ± 1.36 vs. 1.63 ± 0.89 (P = 0.02). Patients in the PEG plus simethicone group showed better bowel cleansing efficacy: BBPS ≥ 6 in 88.3 % vs. 75.2 % (P < 0.001) and bubble scores of 1.00 ± 1.26 vs. 3.98 ± 2.50 (P < 0.001). Abdominal bloating was reported less frequently in the PEG plus simethicone group (7.8 % vs. 19.7 %, P < 0.001) than in the PEG alone group.Conclusion Combined use of PEG and simethicone is associated with a significantly increased ADR in a Chinese population.